ANALISIS KINERJA KEUANGAN SEBELUM DAN SELAMA PANDEMI COVID-19 PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Amelia, Mita; Kusuma, Indra Cahya; Aziz, Ayi Jamaludin (Jurnal Akuntansi Kompetif, 2024)
Abstract: Financial peirformancei is a picturei of a company's financial condition in a ceirtain peiriod. This study aims to deiteirminei thei financial peirformancei of teileicommunications companieis listeid on thei Indoneisia Stock EIxchangei beiforei and during thei Covid-19 pandeimic for thei 2019-2021 peiriod. Thei samplei takein in this study was 4 companieis obtaineid through purposivei sampling teichniqueis. Thei meithod useid is quantitativei deiscriptivei, using financial ratios as a meiasurei of financial peirformancei. Thei reisults of this study show that financial peirformancei beiforei and during thei Covid-19 pandeimic in thei liquidity ratio for EIXCL, FREIN and TLKM companieis fluctuateid whilei ISAT deicreiaseid. Thei solveincy ratio for EIXCL, FREIN and ISAT companieis increiaseid whilei TLKM fluctuateid. Thei activity ratio for FREIN, ISAT and TLKM companieis fluctuateid whilei FREIN deicreiaseid. Thei profitability ratio for EIXCL, FREIN and TLKM companieis increiaseid whilei ISAT fluctuateid. Keiywords: Covid-19 Pandeimic, Financial Peirformancei, Financial Ratio